Buckling analysis in stretchable electronics. (December 2017) - Wang, Bo; Bao, Siyuan; Vinnikova, Sandra; Ghanta, Pravarsha; Wang, Shuodao
Abstract In the last decade, stretchable electronics evolved as a class of novel systems that have electronic performances equal to established semiconductor technologies, but can be stretched, compressed, and twisted like a rubber band. The compliance and stretchability of these electronics allow them to conform and mount to soft, elastic biological organs and tissues, thereby providing attractive opportunities in health care and bio-sensing. Majority of stretchable electronic systems use an elastomeric substrate to carry an ultrathin circuit mesh that consists of sparsely distributed stiff, thin-film electronic components interconnected by various forms of stretchable metal strips or low-dimension materials. During the fabrication processes and application of stretchable electronics, the thin-film components or nanomaterials undergo different kinds of in-plane deformation that often leads to out-of-plane or lateral buckling, in-surface buckling, or a combination of all. A lot of creative concepts and ideas have been developed to control and harness buckling behaviors, commonly regarded as pervasive occurrences in structural designs, to facilitate fabrication of stretchable structures, or to enhance stretchability. This paper provides a brief review of recent progresses on buckling analysis in stretchable electronics. Detailed buckling mechanics reveals important correlations between the geometric/material properties and system performance (e.g., mechanical robustness, deformability, structural architecture, and control). These mechanics models and analysis provide insights to design and optimize stretchable electronics for a wide range of important applications.